I am Sacajawea, I am York : our journey West with Lewis and Clark - Murphy, Claire Rudolf (Walker, 2005)
Sacajawea, a Shoshoni woman, and York, a slave, assist Meriwether Lewis and William Clark on their westward expedition; Sacajawea using her knowledge of the land, and York using his superior hunting skills. When Lewis and Clark's Corps of Discovery set out in the spring of 1804, they had chosen to go on an unprecedented, extremely dangerous journey. It would be the adventure of a lifetime. Unlike others in the group, two key members chose to join the hazardous expedition: York, Clark's slave, and Sacajawea, considered to be the property of Charbonneau, the expedition's translator. The unique knowledge and skills Sacajawea and York had were essential to the success of the trip. The dual stories of these two outsiders, who earned their way into the inner core of the Lewis and Clark Expedition, shed new light on one of the most exciting and important undertakings in American history.